Ilhom THE INTERLEVEL ANALYSIS OF VERBAL HUMOUR RESOURCES IN THE ENGLISH LANGUAGE: THE INTERLEVEL ANALYSIS OF VERBAL HUMOUR RESOURCES IN THE ENGLISH LANGUAGE - Rustamov, Ilhom (Журнал иностранных языков и лингвистики, 2022)
Linguistic mechanism of producing humorous effect has been widely studied by V. Raskin (1985), I. Ermida (2008) and S. Attardo (1994). While providing full insight into the problem of verbal humour, their works, however, lack rigorous classification of units having humour potential. This has prompted us to conduct an interlevel analysis and prove that there are certain resources for humour on each level of the English language.